2023
DOI: 10.1186/s12913-023-09133-z
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Swedish primary health care - a web-based survey exploring patient satisfaction

Abstract: Background Direct-to-consumer telemedicine (TM), with patients having access to a physician via video or text chat, has gradually been introduced into Swedish primary care during the last two decades. Earlier studies have concluded that patients were generally satisfied with TM and the satisfaction rate was consistently above 80% and comparable with in-person visits. Despite the number of studies looking at user experience, studies assessing what factors influence patient satisfaction are lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…A previous study of a Swedish population showed utilization of digital PHC being more common among those of a younger age and women [ 4 ] and a previous study of an American population showed similar results as this study with a mean age of 38.3 years and 63% of users being women [ 6 ]. Furthermore, previous studies have shown older age being associated with impaired digital health literacy [ 10 ] and dissatisfaction with digital PHC [ 23 ]. Meanwhile, elderly patients have also expressed a wish and a need to move forward and learn more about digital solutions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of a Swedish population showed utilization of digital PHC being more common among those of a younger age and women [ 4 ] and a previous study of an American population showed similar results as this study with a mean age of 38.3 years and 63% of users being women [ 6 ]. Furthermore, previous studies have shown older age being associated with impaired digital health literacy [ 10 ] and dissatisfaction with digital PHC [ 23 ]. Meanwhile, elderly patients have also expressed a wish and a need to move forward and learn more about digital solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial associations, age and occupational status were not overall significantly associated with satisfaction in the multivariable analyses, suggesting they were correlated with other factors. Multivariable exploration of the association with age in other samples will be useful, particularly given the mixed findings in previous studies (12,13,(15)(16)(17)(18). Given the limited representation of those from ethnic minority groups in the present study, further exploration of satisfaction with remote GP consultations by ethnic background would be useful.…”
Section: Implications For Research And/or Practicementioning
confidence: 90%
“…Studies exploring demographic variation in satisfaction with remote primary care consultations during the COVID-19 pandemic have used a variety of satisfaction measures, often using single items (11)(12)(13)(14)(15)18). Those which used multi-item measures of satisfaction do not appear to have included factors specific to COVID-19 (16,17).…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, innovative technologies, including telemedicine and digital health records, have also been embraced by leading healthcare systems in the world 5 . For instance, Scandinavian countries have integrated telemedicine platforms into their emergency trauma care protocols, enabling real-time consultations and streamlined information sharing between healthcare providers 14 . In times of disaster management, this service would be of utmost importance.…”
mentioning
confidence: 99%